MRI essentials in epileptology: a review from the ILAE Imaging Taskforce. Issue 4 (19th September 2020) - Wang, Irene; Bernasconi, Andrea; Bernhardt, Boris; Blumenfeld, Hal; Cendes, Fernando; Chinvarun, Yotin; Jackson, Graeme; Morgan, Victoria; Rampp, Stefan; Vaudano, Anna Elisabetta; Federico, Paolo
Abstract: Magnetic resonance imaging (MRI) plays a central role in the management and evaluation of patients with epilepsy. It is important that structural MRI scans are optimally acquired and carefully reviewed by trained experts within the context of all available clinical data. The aim of this review is to discuss the essentials of MRI that will be useful to health care providers specialized in epilepsy, as outlined by the competencies and learning objectives of the recently developed ILAE curriculum. This review contains information on basic MRI principles, sequences, field strengths and safety, when to perform and repeat an MRI, epilepsy MRI protocol (HARNESS‐MRI) and the basic reading guidelines, and common epileptic pathologies. More advanced topics such as MRI‐negative epilepsy, functional MRI and diffusion‐weighted imaging are also briefly discussed. Although the available resources can differ markedly across different centers, it is the hope that this review can provide general guidance in the everyday practice of using MRI for patients with epilepsy.